Ultrastructure of the organ of Corti in harbor seals (Phoca vitulina) - Rojas, Laura; Haulena, Martin; Reichmuth, Colleen; Busse, Björn; Ramos-Garduño, L. Aurora; Rico-Chávez, Oscar; Siebert, Ursula; Morell, Maria (Frontiers in Marine Science, 2023)
Ultrastructural descriptions of the inner ear of highly sound-dependent mammalian species are lacking and needed to gain a better understanding of the hearing sense. Here, we present the first morphometric descriptions of the sensory cells of the inner ear in the harbor seal (Phoca vitulina), a mammal with broadly sensitive amphibious hearing. Scanning electron micrographs of the apical surface of the outer hair cells (OHCs) and inner hair cells (IHCs) within the organ of Corti were obtained from five individuals and analyzed by linear and geometric morphometrics. Measurements were taken at regular locations along the cochlea. The spiral shape of the seal cochlea contained two and a half turns. The organ of Corti had an average length of 27.7 mm with 12,628 OHCs (12,400-12,900). Six linear morphometric parameters showed significant patterns of change associated with their location within the cochlear spiral. Likewise, these trends were similarly expressed in cell configuration (cell blocks with 57 landmarks in 12 representative cells) revealed by geometric morphometry. Cell configuration varied predictably with position in the cochlea according to clustering analyses and Procrustes ANOVA (F= 25.936, p<0001). Changes associated with OHCs were primarily responsible for observed changes in cell configuration. An integration trend in cell shape change was also observed in which IHCs and OHCs share features in their morphological variation by the two-block partial least squares analysis (CR=0.987, p<0.001) and the modularity hypothesis (CV=0.99, p=0.05). These descriptive and quantitative findings provide a baseline for the morphology and morphometry of the sensory cells of the organ of Corti in harbor seals, allowing for comparisons between normal and pathological features. This initial morphological description should enable the correlation between position, morphometric features, and frequency coding along the spiral of the inner ear in this species, whose hearing ability is well studied.